Impediments faced by South African financiers in granting credit finance to SMMEs - Kiwanuka, Kabito Baker (My University, 2012)
The Small, Medium and Micro Enterprise (SMME) sector has a positive role to play in the South African economy. It is through this sector that the challenges of job creation, economic growth, and financial equity can be dealt with. Through legislative and policy frameworks, the post-apartheid South African government has led to the creation of government-backed SMME support institutions that would foster the growth of a favourable economic environment to support SMME growth. However various perspectives and opinions on the constraints hindering SMME growth have been advanced, one of which is the alleged conservativeness of commercial banks in dealing with SMMEs. This study follows a qualitative research methodology approach towards investigating the impediments faced by financial institutions in servicing the SMME sector. The research findings identified poorly motivated business plans, unrealistic market research, poor credit records of applicants and a lack of management skills training and collateral as the impediments that hinder financial institutions from servicing SMMEs. These findings are in contention with the perceived conservativeness of financial institutions when dealing with SMMEs as advocated by most authors in the literature. Furthermore, the research findings highlight the fact that financial institutions should be included as joint interests in any policy and legislative framework formation that is aimed at easing access to credit finance by SMMEs.
MBA thesis - WBS
Keywords: Credit financing; Small medium and micro businesses; SMMEs; Financing of businesses